The 4D nucleome: Evidence for a dynamic nuclear landscape based on co-aligned active and inactive nuclear compartments - Cremer, Thomas; Cremer, Marion; Hübner, Barbara; Strickfaden, Hilmar; Smeets, Daniel; Popken, Jens; Sterr, Michael; Markaki, Yolanda; Rippe, Karsten; Cremer, Christoph (FEBS letters, 2015)
Recent methodological advancements in microscopy and DNA sequencing-based methods provide unprecedented new insights into the spatio-temporal relationships between chromatin and nuclear machineries. We discuss a model of the underlying functional nuclear organization derived mostly from electron and super-resolved fluorescence microscopy studies. It is based on two spatially co-aligned, active and inactive nuclear compartments (ANC and INC). The INC comprises the compact, transcriptionally inactive core of chromatin domain clusters (CDCs). The ANC is formed by the transcriptionally active periphery of CDCs, called the perichromatin region (PR), and the interchromatin compartment (IC). The IC is connected to nuclear pores and serves nuclear import and export functions. The ANC is the major site of RNA synthesis. It is highly enriched in epigenetic marks for transcriptionally competent chromatin and RNA Polymerase II. Marks for silent chromatin are enriched in the INC. Multi-scale cross-correlation spectroscopy suggests that nuclear architecture resembles a random obstacle network for diffusing proteins. An increased dwell time of proteins and protein complexes within the ANC may help to limit genome scanning by factors or factor complexes to DNA exposed within the ANC.
Gesehen am 10.12.2020